The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1145/1314215.1314223
|View full text |Cite
|
Sign up to set email alerts
|

IT diffusion in developing countries

Abstract: here is widespread belief among international agencies and development specialists in the potential value of information technology (IT) to support economic and human development [11,12]. Some question whether IT alone can have a major impact on the standard of living in developing countries, but most see it offering access to vital information and services such as weather forecasting, commodity prices, health care, and education. However, a significant digital divide exists between richer and poorer countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…Also, it was noted by Shih et al (2008) that the productivity and economic growth in developed countries in general and the United States in particular is derived by investment in information technology. However, it is not a significant driver in developing countries.…”
Section: It/is In Developing Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it was noted by Shih et al (2008) that the productivity and economic growth in developed countries in general and the United States in particular is derived by investment in information technology. However, it is not a significant driver in developing countries.…”
Section: It/is In Developing Countriesmentioning
confidence: 99%
“…They found a negative correlation between IT investment and interest rates, but positive and significant correlation between telecommunications infrastructure, investment, and openness to trade. Also, Shih et al (2008) discussed the need for implementing information technology effectively in developing countries in order to support economic and human development. Their results concluded that wealth is the most significant factor influencing IT investment.…”
Section: It/is In Developing Countriesmentioning
confidence: 99%
“…This IT resource will have immediate effect on organizations' business processes. This is possible because acquired IT resources will be mature and well-tested in competitive markets (Shih et al, 2008). As with developed countries, investment in IT in LDEs is a strategic necessity, but in LDE's, per se, it can also be a source of their business value.…”
Section: Hypotheses Development 31mentioning
confidence: 99%
“…The gap in access to IT resources is large across the developing countries (Walsham et al, 2007, Walsham, 2010. This disparity is increasingly becoming evident as fast growth in large emerging markets like Brazil, China, and India mask slower development elsewhere (Shih et al, 2008). This disparity is also evident within some developing economies where certain sectors of the population are deprived of access to the IT resources (Walsham, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation